Musashi: Takezo the Ronin, Aggression, and Erich Fromm's Psychological Perspective - Anas Ahmadi (IZUMI, 2021)
This study explores the character of Takezo the ronin in Musashi by Eiji Yoshikawa through the psychological perspective of aggression. This research specifically aims to (a) explore Takezo's psychology of aggression as a ronin and (b) the impact of Takezo's aggression on others. The approaches used in this research are the psychology of literacy and the psychology of aggression. The method used is qualitative; it uses data exposure and interpretation. The data source is the novel Musashi by Eiji Yoshikawa (translated version in Indonesian). The data used is in the form of text that is relevant to Takezo's psychology of aggression. The data analysis techniques are carried out in five stages, (1) identifying data related to Takezo's psychology of aggression, (2) data classification related to Takezo's psychology of aggression, (3) data presentation related to Takezo's psychology of aggression, and (4) summarizing data related to Takezo's psychology of aggression. The results showed that Takezo's aggressions are represented in the form of thoughts and behaviour. Takezo's aggressive thoughts are wanting to defeat and kill his enemies. Takezo's aggressive behaviour is killing his enemies, who are samurai. Takezo's aggressions cause the impact of physical category, and they are death and disability on the defeated samurai. Besides, in the psychological category, Takezo's aggressions cause fear and hatred in society. It is concluded that Takezo represents ronin, which desires destructive aggression that has a physical and psychological impact on others.